Genetic interrelationships among phosphorus, nitrogen, calcium, and energy bioavailability in a growing chicken population - Ankra-Badu, G.A.; Pesti, G.M.; Aggrey, S.E. (Poult Sci. 89(11): 2351-5, 2010)
A random-mating population was used to study the genetic interrelationship between phytate P (PPB), Ca (CaB), N (NB), and energy bioavailability (EB), BW at 4 wk of age, relative growth (RG), and feed conversion ratio (FCR). Heritability estimates for PPB, CaB, NB, and EB were 0.09, 0.13, 0.16, and 0.10, respectively, and those of BW, RG, and FCR were 0.66, 0.15, and 0.10, respectively. Genetic correlations between PPB and BW, and FCR were moderate and negative, suggesting that improvement in PPB will impair growth. The genetic correlations between PPB and CaB, and EB and RG were positive and moderate, indicating that improvement in PPB would also lead to improved CaB, EB, and RG. Energy bioavailability was positively correlated with CaB, NB, PPB, and BW. Even though the genetic correlation between EB and the other traits measured, except RG and FCR, ranged from low to moderate, improving the ability of birds to utilize caloric energy in the feed would consequently improve PPB as well as growth. Improving PPB would reduce the amount of P in excreta and provide an additional savings if exogenous phytase were not added to poultry feed. The genetic correlation between PPB and NB was low but positive, whereas NB had a positive genetic correlation with BW. Therefore, selecting on NB will result in positive correlated responses in BW and PPB. Improving PPB and NB will not only improve productivity, but also reduce the polluting effects of P and N on the environment.